Octenidine-based hydrogel shows anti-inflammatory and protease-inhibitory capacities in wounded human skin - Saskia Seiser (Nature Portfolio, 2021)
Abstract Octenidine dihydrochloride (OCT) is a widely used antiseptic molecule, promoting skin wound healing accompanied with improved scar quality after surgical procedures. However, the mechanisms by which OCT is contributing to tissue regeneration are not yet completely clear. In this study, we have used a superficial wound model by tape stripping of ex vivo human skin. Protein profiles of wounded skin biopsies treated with OCT-containing hydrogel and the released secretome were analyzed using liquid chromatography-mass spectrometry (LC–MS) and enzyme-linked immunosorbent assay (ELISA), respectively. Proteomics analysis of OCT-treated skin wounds revealed significant lower levels of key players in tissue remodeling as well as reepithelization after wounding such as pro-inflammatory cytokines (IL-8, IL-6) and matrix-metalloproteinases (MMP1, MMP2, MMP3, MMP9) when compared to controls. In addition, enzymatic activity of several released MMPs into culture supernatants was significantly lower in OCT-treated samples. Our data give insights on the mode of action based on which OCT positively influences wound healing and identified anti-inflammatory and protease-inhibitory activities of OCT.